Causing Factors of Degenerative Disease towards Elderly Women - Irwanti Gustina; Putri Sarah Dita (STIKes Patria Husada Blitar, 2021)
The proportion of the elderly population in Indonesia has a positive or negative impact, it is said to be positive if the elderly population is in a healthy, active and productive condition. The elderly become a burden if they have health problems such as degenerative diseases. In this study, the authors looked for the Causes of Degenerative Disease in Elderly Women. This study used 50 elderly women for sample. This research design used cross sectional, data collection techniques through questionnaires. The results showed that there was a significant correlation between degenerative diseases in the elderly with diet, physical activity, rest patterns, and health care support for the elderly. Meanwhile, smoking habit with p-value = 0.283 meant that statistically there was no correlation between smoking habits and degenerative diseases, this was because the proportion of elderly women who smoke and had degenerative diseases was less. The conclusion of the research was the productivity of women in youth and lifestyle had an effect on women's health in old age.